The usefulness of the oral components of ULAB3162 in enhancing students' oral communication skills - Seri Izati Mohamad Khata, 1996-, author; Rohani Othman, 1962-, supervisor 603736; Fakulti Sains Sosial dan Kemanusiaan. Sekolah Pendidikan 619083 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains Serta Pendidikan (TESL)) - Universiti Teknologi Malaysia, 2019